1997
DOI: 10.1002/(sici)1096-9071(199705)52:1<97::aid-jmv16>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus specific serum antibodies in infants under six months of age: Limited serological response upon infection

Abstract: The decline of maternal respiratory syncytial virus (RSV) specific serum antibodies was studied in 45 children during the first 6 months of life, using a virus neutralization assay and competition ELISAs measuring fusion protein and glycoprotein specific antibodies. In all children RSV neutralizing antibodies were demonstrated at birth, with titers ranging from 33 to 1382. The calculated mean half life of these antibodies was 26 days. Furthermore, in a group of 38 children with suspected RSV infection, all you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
100
3
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(112 citation statements)
references
References 20 publications
7
100
3
2
Order By: Relevance
“…The lower magnitude of the humoral immune response to RSV in children <3 months may suggest that: i) maternal antibodies may interfere with IgG-producing cells and mediate a temporary immunosuppression in infants; ii) most of the children <3 months are not able to produce sufficiently high antibody titers to be protected; iii) in most cases maternal antibodies did not have enough neutralizing activity against the RSV strains which caused the infections. Brandenburg et al (18) found variable titers of neutralizing antibodies (33 to 1382) in infants at birth, a fact that could explain, at least in part, why some children produce RSV-specific antibodies and others do not.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The lower magnitude of the humoral immune response to RSV in children <3 months may suggest that: i) maternal antibodies may interfere with IgG-producing cells and mediate a temporary immunosuppression in infants; ii) most of the children <3 months are not able to produce sufficiently high antibody titers to be protected; iii) in most cases maternal antibodies did not have enough neutralizing activity against the RSV strains which caused the infections. Brandenburg et al (18) found variable titers of neutralizing antibodies (33 to 1382) in infants at birth, a fact that could explain, at least in part, why some children produce RSV-specific antibodies and others do not.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in RSV-specific antibodies detected in infants <1 month to 6 months of age is consistent with the loss of maternal antibodies, as reported previously (5,18). In the present study, examination of sera from RSV-infected children revealed that the total IgG levels were higher than IgG1 levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of maternal antibodies in the transmission of hRSV at the population level is uncertain. It has been shown that higher levels of maternal antibodies are associated with increased protection from clinical infection [24], but this association is partial and probably short term (maternal antibodies are only present for 3-6 months [25]). For the purposes of the model presented, it is assumed that maternal antibodies have negligible effect on the transmission of the virus in the whole population.…”
Section: Model Structurementioning
confidence: 99%